2022
DOI: 10.1590/1806-9282.20211007
|View full text |Cite
|
Sign up to set email alerts
|

Constipation in the period of limited isolation during COVID-19 pandemic

Abstract: OBJECTIVE: COVID-19 outbreak has become widespread globally and caused a new global chaos. This outbreak that completely affected the lifestyle of individuals resulted in periods of isolation. Here, we evaluated the effects of lifestyle changes with isolation on constipation. METHODS: A survey on constipation was performed during the 12-week isolation period starting in March 2020 in Turkey. Data of 390 individuals who participated in the survey through the social media and who were actively employed prior to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Kayaoglu et al 31 revealed a decrease in CIC prevalence after social isolation of 15.1 to 1.3% in the general population. Remes-Troche et al, 32 on the other hand, evidenced in 1.110 volunteers the appearance of complains related to constipation in 25% after 4 weeks of social isolation.…”
Section: Discussionmentioning
confidence: 99%
“…Kayaoglu et al 31 revealed a decrease in CIC prevalence after social isolation of 15.1 to 1.3% in the general population. Remes-Troche et al, 32 on the other hand, evidenced in 1.110 volunteers the appearance of complains related to constipation in 25% after 4 weeks of social isolation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the survey on the social and psychological balance dimensions showed that patients with functional constipation rarely share personal problems or concerns with others nor discuss constipation with their families. Some investigations have shown that psychological stress and social disorder easily cause constipation ( 25 , 26 ) and anxiety tends to have a negative impact on their daily life ( 27 ). However, patients in the control group diagnosed with functional constipation were managed by their responsible nurse and doctor, their specific treatment measures were dominated by medical personnel.…”
Section: Discussionmentioning
confidence: 99%
“…Constipation is a common clinical condition in gastroenterological practice, estimated to affect up to 16% of the world’s population 1. It is characterised by infrequent and/or difficult bowel emptying, excessive straining, reduced bowel movements or a feeling of incomplete voiding, often accompanied by straining or a sensation of incomplete bowel movements 1 2. The occurrence of constipation is complex and multifactorial 3.…”
Section: Introductionmentioning
confidence: 99%